Exploring the Global Landscape of Nurses' Knowledge, Attitude and Competence in Palliative Care: A Scoping Review - Ayu Hardanti; Erna Rochmawati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: In palliative care, nurses have essential roles in addressing complex needs of patients with palliative care needs that include physical, psychological, social and spiritual needs. Knowledge and competence are deeply interconnected, as both are critical to provide quality care to patients with life-limiting conditions. However, a comprehensive exploration of nurses’ knowledge, attitude and competence in palliative care across regions remains lacking. The aim of this scoping is to systematically map the existing evidence regarding palliative care knowledge, attitude and competence among nurses. Method: This review followed scoping review framework from Arskey and O’Malley. The PCC framework (population, concept and context) was applied; Population – nurse; Concept- knowledge, competence and attitude; and Context – palliative care. A comprehensive search was conducted in several data bases: PubMed, SCOPUS, Science Direct, and ProQuest. The search criteria were restricted to studies published in English between 2000 and 2024. Thematic analysis was used to map themes. Results: Thirty studies were included in review, demonstrate a consistent pattern of nurses’ insufficient knowledge and self-perceived competence in palliative care, particularly in psychological and spiritual domains. Across studies, assessment approaches were methodologically homogeneous, with a predominant reliance on cross-sectional designs and self-administered instruments. The Palliative Care Knowledge Test (PCKT)) and the Palliative Care Quiz for Nurses (PCQN emerged as the most frequently used tools to measure knowledge, while the Palliative Care Nursing Self-Competence Scale was commonly employed to assess competence. Conclusion: The review identified nurses’ knowledge ranged from low to moderate with lower competence reported in specific areas such as spiritual care. The findings emphasized the need to equip nurses with adequate knowledge and competencies in palliative care to ensure quality care for patients and family caregivers in palliative care setting.